The Cholesterol-Lowering Effect of Alisol Acetates Based on HMG-CoA Reductase and Its Molecular Mechanism. (30th October 2016) - Xu, Fei; Yu, Hui; Lu, Cai; Chen, Jun; Gu, Wei
Abstract : This study measured the impact of alisol B 23-acetate and alisol A 24-acetate, the main active ingredients of the traditional Chinese medicine Alismatis rhizoma, on total cholesterol (TC), triglyceride (TG), high density lipoprotein-cholesterol (HDL-C), and low density lipoprotein-cholesterol (LDL-C) levels of hyperlipidemic mice. The binding of alisol B 23-acetate and alisol A 24-acetate to the key enzyme involved in the metabolism of TC, 3-hydroxy-3-methylglutary-coenzyme A (HMG-CoA) reductase, was studied using the reagent kit method and the western blotting technique combined with a molecular simulation technique. According to the results, alisol acetates significantly lower the TC, TG, and LDL-C concentrations of hyperlipidemic mice, while raising HDL-C concentrations. Alisol acetates lower HMG-CoA reductase activity in a dose-dependent fashion, both in vivo and in vitro . Neither of these alisol acetates significantly lower the protein expression of HMG-CoA. This suggests that alisol acetates lower the TC level via inhibiting the activity of HMG-CoA reductase by its prototype drug, which may exhibit an inhibition effect via directly and competitively binding to HMG-CoA. The side chain of the alisol acetate was the steering group via molecular simulation.